2020
DOI: 10.3390/ijms21207781
|View full text |Cite
|
Sign up to set email alerts
|

Toward G-Quadruplex-Based Anticancer Agents: Biophysical and Biological Studies of Novel AS1411 Derivatives

Abstract: Certain G-quadruplex forming guanine-rich oligonucleotides (GROs), including AS1411, are endowed with cancer-selective antiproliferative activity. They are known to bind to nucleolin protein, resulting in the inhibition of nucleolin-mediated phenomena. However, multiple nucleolin-independent biological effects of GROs have also been reported, allowing them to be considered promising candidates for multi-targeted cancer therapy. Herein, with the aim of optimizing AS1411 structural features to find GROs with imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…Other AS1411 derivatives, with greater resistance to nucleases can also be used as potential carriers of anticancer drugs. For instance, four new derivatives (AS1411-G, AS1411-GT, AS1411-GT-T8 and AS1411-GT-5′tr) were proposed in order to optimize AS1411 structural features and to find G-rich sequences to improve anticancer properties [ 46 ]. Three of them (AS1411-G, AS1411-GT and AS1411-GT-T8) have eight G-tracts, which in principle may allow the formation of two tandem G4s connected by a linker [ 46 ].…”
Section: G-quadruplex Structures As Drug Delivery Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other AS1411 derivatives, with greater resistance to nucleases can also be used as potential carriers of anticancer drugs. For instance, four new derivatives (AS1411-G, AS1411-GT, AS1411-GT-T8 and AS1411-GT-5′tr) were proposed in order to optimize AS1411 structural features and to find G-rich sequences to improve anticancer properties [ 46 ]. Three of them (AS1411-G, AS1411-GT and AS1411-GT-T8) have eight G-tracts, which in principle may allow the formation of two tandem G4s connected by a linker [ 46 ].…”
Section: G-quadruplex Structures As Drug Delivery Systemsmentioning
confidence: 99%
“…For instance, four new derivatives (AS1411-G, AS1411-GT, AS1411-GT-T8 and AS1411-GT-5′tr) were proposed in order to optimize AS1411 structural features and to find G-rich sequences to improve anticancer properties [ 46 ]. Three of them (AS1411-G, AS1411-GT and AS1411-GT-T8) have eight G-tracts, which in principle may allow the formation of two tandem G4s connected by a linker [ 46 ]. The four derivatives showed higher thermal stability and inhibitory effect against topoisomerase I than AS1411 [ 46 ].…”
Section: G-quadruplex Structures As Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some more derivatives of AS1411 with anti-proliferative activity toward MCF-7 cells have been developed [ 12 ]. GQs with three-tetrad structures were 10 times more active than the initial AS1411 with two-tetrad GQ.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a covalent bi-modular version of the sequence [G 3 (TG 3 ) 3 ] has proven to possess anti-proliferative activity for the neural cancer cell line U87 [25]. Contrary to the significant number of studies concerning the antiproliferative aptamers AS1411 [26,27] (and its analogues [28,29]) and TBA [20] (and its derivatives [30][31][32][33][34][35][36][37][38]), only limited comparable investigations have regarded other aptamers. For example, in the case of the aptamer T30175, no research concerning potential antiproliferative properties has been reported to date, although its sequence partially overlaps those of EAD and S13 and its structure is strictly correlated to that of T30923, as demonstrated by CD (Circular Dichroism), NMR (Nuclear Magnetic Resonance), gel electrophoresis, and molecular dynamics simulations [9,10,39].…”
Section: Introductionmentioning
confidence: 99%